Reseña de: Gregori, Gian Luca – Almagno, Giovanii, Roman Calendars: Imperial Birthdays, Victories and Triumph - Novillo López, Miguel Ángel (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2019)
Reseña de: Gregori, Gian Luca – Almagno, Giovanii, Roman Calendars: Imperial Birthdays, Victories and Triumphs, Beau-Bassin, LAP-Lambert Academic Publishing, 2019, 182 pp., ISBN: 978-613-9-44296-6.